Design of microstrip lowpass filter at 3 GHz for wireless communications / Normasni Ad Fauzi - Ad Fauzi, Normasni (2004)
The purposes of this project are to design, simulate, fabricate and measuring the output response of the Microstrip Lowpass Filter. The filter is intended to operate with cut-off frequency of 3 GHz, a stopband attenuation of 30 dB and 0.5 dB of passband attenuation. The ripple passband is to be 0.0432 dB. The major design process is aided by CAD packages called HP/Eesof Libra and Sonnet Lite. The microstrip laminates used as 'Duroid/Rogers 5872' with 0.5 mm substrate thickness and relative permittivity ^r equal to 2.33. The filter is then measured using a Wiltron Scalar Network Analyzer to obtain its characteristics.